SAFETALK PRACTICES IN CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL) CLASSES - Fitriati, Sri Wuli (Language Circle: Journal of Language and Literature, 2016)
This article is drawn from a larger ethnographic case study of a state senior high school in a city in the province of Central Java, Indonesia. The study was classroom discourse analysis, focusing on identifying and examining classroom interactional and pedagogical practices in Content and Language Integrated Learning (CLIL) lessons. CLIL is a type of bilingual education in which some content areas (such as Sciences) are learned through a foreign language. The research participants in this study were Indonesian teachers of Mathematics, Biology, and Geography who were encouraged to teach their subjects in English language because of the political ideology and educational policy at the time the data collected. The data emerged from classroom observations notes, lesson transcripts, and post-lesson interviews with video-stimulated recall. The interpretation and analysis of the data involved cross-checking different sources of evidence. Braun and Clarkeâs thematic analysis (2006) was employed in the analysis of the data. The finding reveals that there was a salient pattern in the interactional and pedagogical practices of the subject teachers which can be called safetalk. The finding also shows that safetalk hinder the studentsâ second language acquisition and development. This article offers deeper insights on the interaction and pedagogy in CLIL classes, which can promote critical reflection and contribute to future English bilingual teacher education, particularly in the Indonesian educational contexts.